2003
DOI: 10.1063/1.1583733
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of flow-induced forces on a circular cylinder using a detached splitter plate

Abstract: Control of flow-induced forces on a circular cylinder using a detached splitter plate is numerically studied for laminar flow. A splitter plate with the same length as the cylinder diameter is placed horizontally in the wake region. Suppressing the vortex shedding, the plate significantly reduces drag force and lift fluctuation; there exists an optimal location of the plate for maximum reduction. However, they sharply increase as the plate is placed further downstream of the optimal location. This trend is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(66 citation statements)
references
References 9 publications
8
57
0
1
Order By: Relevance
“…Looking at our baseline case for SSG at U ∞ = 11 m/s for consistency, we find that for x sp /t 0 = 3 the value of T u peak decreases from 0.146 to 0.107, a reduction of 27%. Moreover, x sp /t 0 = 3 is close to x sp /D = 2.5 − 2.7, which was found to be the optimal distance for suppressing vortex shedding from a circular cylinder (see Roshko, 1954;Lin and Wu, 1994;Hwang et al, 2003).…”
Section: Vortex Shedding Suppressionmentioning
confidence: 99%
“…Looking at our baseline case for SSG at U ∞ = 11 m/s for consistency, we find that for x sp /t 0 = 3 the value of T u peak decreases from 0.146 to 0.107, a reduction of 27%. Moreover, x sp /t 0 = 3 is close to x sp /D = 2.5 − 2.7, which was found to be the optimal distance for suppressing vortex shedding from a circular cylinder (see Roshko, 1954;Lin and Wu, 1994;Hwang et al, 2003).…”
Section: Vortex Shedding Suppressionmentioning
confidence: 99%
“…Theposition and length of ribbons have a significant effect on the drag reduction. Hwang et al [7] applied a detached splitter plate for the control of flowinduced forces on a circular cylinder in their numerical study of laminar flow. They revealed that optimal location of splitter plate reduces the drag coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of VIV amplitude is a method that reduces stresses and fatigue damage which can be achieved using different ways such as increasing structural damping, avoiding resonance and manipulate the wake. [5]), shrouds (Zdravkovich [6]), splitter plate (Hwang et al [7]), rear-wake stabilizer (Eisenlohr and Eckelmann [8]), and small rods (Zhao et al [9]; Zhao et al [10]). Geometric modifications of cylinder wall are the main methods for these passive controls, which inevitably increase the mass ratio and sometimes increase the drag coefficient (e.g., helical strake).…”
Section: Introductionmentioning
confidence: 99%